2006
DOI: 10.1562/2006-02-10-ra-801
|View full text |Cite
|
Sign up to set email alerts
|

UVA and UVB Decrease the Expression of CD44 and Hyaluronate in Mouse Epidermis, which is Counteracted by Topical Retinoids

Abstract: The transmembrane glycoprotein CD44 is currently thought to be the main cell surface receptor for the glycosaminoglycan hyaluronate. We previously showed that (1) CD44 regulate keratinocyte proliferation; (2) topical retinoids dramatically increase the expression of CD44, hyaluronate and hyaluronate synthase (HAS)s in mouse epidermis; (3) topical retinaldehyde restores the epidermal thickness and CD44 expression which are correlated with clinical improvement in lichen sclerosus et atrophicus lesions; and (4) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 37 publications
(45 reference statements)
4
31
1
2
Order By: Relevance
“…12,35 In addition, it has been shown recently that UVA and UVB irradiation decrease epidermal HA and CD44 in mice. 38 In contrast only a few biochemical and histological studies addressed the effect of UV irradiation on HA content of murine and human dermis. Some studies reported increased HA content in UV-irradiated skin of mice, 39,40 whereas others reported reduced HA content.…”
Section: Discussionmentioning
confidence: 99%
“…12,35 In addition, it has been shown recently that UVA and UVB irradiation decrease epidermal HA and CD44 in mice. 38 In contrast only a few biochemical and histological studies addressed the effect of UV irradiation on HA content of murine and human dermis. Some studies reported increased HA content in UV-irradiated skin of mice, 39,40 whereas others reported reduced HA content.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that UVA or UVB irradiation significantly decreased the content of HA and the expression of its receptor CD44 (see below) in the epidermis of hairless mice [28]. …”
Section: Potential Mechanisms Of Skin Fragility In Dermatoporosismentioning
confidence: 99%
“…Moreover, CD44 expression is reduced with exposure to UV light. This reduced expression of CD44 can be reversed by retinoids such retinol or retinaldehyde [30,31].…”
Section: Introductionmentioning
confidence: 99%